Effect of copper ions on sulfidization flotation of smithsonite: Surface properties and adsorption mechanism - Zhao, Wenjuan; Yang, Bin; Liu, Dianwen; Feng, Qicheng (Colloids and surfaces. A, Physicochemical and engineering aspects, 2022)
This work proposed a promising method to increase the flotation recovery of smithsonite in the sulfidization xanthate system by activation with copper ions prior to addition of Na2S. The effect of copper ions on surface properties, sulfide adsorption, and floatability of smithsonite was examined using micro-flotation experiments, solution composition determination, and surface measurements. The flotation recovery of smithsonite activated by copper ions was superior to that in the direct sulfidization system, along with a maximum increase by approximately 19%. It was ascribed to an increase in active sites on smithsonite surfaces due to the formation of –O–Cu complexes. Cu2+ in the pulp solution bonded to O sites on smithsonite surfaces, and Cu(OH)+ interacted with –OH species through dehydration reaction to form activation products. It was beneficial to the interaction of sulfide species with smithsonite surfaces, and more sulfidization products formed on the mineral surface. The sulfidization products were composed of copper sulfide and zinc sulfide species in the enhanced sulfidization system, and copper sulfide species exhibited higher affinity to xanthate than zinc sulfide. It greatly improved the surface hydrophobicity of smithsonite after enhanced sulfidization with copper ions, thereby promoting the flotation recovery of smithsonite, which is significant for the sustainable production of refractory zinc oxide ores. [Display omitted] •Copper species could interact with O sites on smithsonite surfaces to produce –O–Cu complexes.•Both copper sulfide and zinc sulfide species formed on smithsonite surfaces after enhanced sulfidization.•More sulfide species adsorbed on smithsonite surfaces with copper ions.•Flotation recovery of smithsonite was significantly increased after activation by copper ions.